The Impact of Single Gene and Chromosomal Disorders on Hospital Admissions of Children and Adolescents: A Population-Based Study - Dye, Danielle; Brameld, Kate; Maxwell, S.; Goldblatt, J.; Bower, C.; Leonard, H.; Bourke, J.; Glasson, E.J.; O'Leary, Peter (S. Karger AG, Basel, 2010)
Background: It is well recognized that genetic disease makes a significant contribution to childhood illness. Here, we present recent population data describing the impact of single gene and chromosomal disorders on hospital admissions of children and adolescents. Methods: Hospital admissions for patients aged 0–19 years between 2000 and 2006, with a single gene or chromosomal disorder, were extracted from the Western Australian Hospital Morbidity Data System using 296 diagnosis codes identified from the International Statistical Classification of Diseases, Tenth Revision, Australian Modification. Data extracted for each patient included the number, length and cost of all admissions.Results: Between 2000 and 2006, 14,197 admissions were identified for 3,271 patients aged 0–19 years with single gene and chromosomal disorders, representing 2.6% of admissions and 4.3% of total hospital costs in this age group. Patients with genetic disorders had more admissions and stayed longer in hospital than patients admitted for any reason. Specific disorders associated with a high demand on hospital services included cystic fibrosis, Down syndrome, osteogenesis imperfecta, thalassemia, and von Willebrand’s disease. Conclusions: Children and adolescents with single gene and chromosomal disorders placed higher demands on hospital services than other patients in their age group, but were responsible for a relatively small proportion of hospital admissions and costs. These data will enable informed planning of health care services for patients with single gene and chromosomal disorders in Western Australia.